Hedging strategies for Icelandic corporations to manage market risk - Case study Orkuveita Reykjavíkur - Matthías Óskarsson 1997-; Skafti Þorvaldsson 1996- (2019)
The aim of this study was to analyze if hedging strategies are a reliable option to manage systematic risk for Icelandic firms. Where a case study on risk management at Orkuveita Reykjavíkur was made to understand a real-life scenario on how risk factors are identified, risk policy and controls are implemented and finally, assessment on the progress and results. Financial statements from firms listed on Nasdaq OMX, First North and four energy firms in Iceland were gathered. Firms ratio in foreign debt and revenue was identified, risk factors- and hedging strategies were defined for each firm and correlation test run. The results of the study show that firms using financial derivatives are justifiably doing that to hedge their risk exposure. The firms that are not conducting any hedging strategies do not share similarities, in the operational environment, with the ones that implemented hedging strategies. It was noticeable that the majority of firms that have debt and revenue streams in foreign currency or identify commodity price risk as one of their systematic risk factors use derivatives as hedging instruments. Keywords: Afleiður Orkuveita Reykjavíkur Áhætta Derivatives(Finance) Case study Risk management